2020
DOI: 10.1016/j.annonc.2020.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Phase I, first-in-human study of futibatinib, a highly selective, irreversible FGFR1–4 inhibitor in patients with advanced solid tumors

Abstract: Background: Futibatinib is an oral, irreversible, highly selective fibroblast growth factor receptor (FGFR)1e4 inhibitor with potent preclinical activity against tumors harboring FGFR aberrations. This first-in-human, phase I dose-escalation trial (NCT02052778) evaluates the safety and pharmacokinetics/pharmacodynamics of futibatinib in advanced solid tumors. Patients and methods: Following a standard 3þ3 dose-escalation design, eligible patients with advanced solid tumors refractory to standard therapies rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
155
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(170 citation statements)
references
References 17 publications
13
155
0
2
Order By: Relevance
“…Futibatinib (TAS-120) is an oral irreversible pan-FGFR inhibitor (FGFR1–4). The phase I FOENIX-101 trial showed partial responses in FGFR2 fusion-positive iCCA patients who had shown refractoriness to standard chemotherapy [ 64 ]. Besides, promising results were obtained in iCCA patients with acquired resistance to other FGFR inhibitors [ 50 ].…”
Section: Response Of Cca To Targeted Therapymentioning
confidence: 99%
“…Futibatinib (TAS-120) is an oral irreversible pan-FGFR inhibitor (FGFR1–4). The phase I FOENIX-101 trial showed partial responses in FGFR2 fusion-positive iCCA patients who had shown refractoriness to standard chemotherapy [ 64 ]. Besides, promising results were obtained in iCCA patients with acquired resistance to other FGFR inhibitors [ 50 ].…”
Section: Response Of Cca To Targeted Therapymentioning
confidence: 99%
“…harboring FGFR aberrations is futibatinib, an irreversible FGFR1-4 inhibitor, which is currently being evaluated in phase II/III trials across multiple histologies [12]. Preliminary analysis of FOENIX-CCA2 (NCT02052778), a single-arm multicenter phase II study evaluating futibatinib in patients with IHCCA and FGFR2 fusions or rearrangements, demonstrated a 37.3% objective response rate (ORR) and 82% disease control rate (DCR) [13].…”
Section: Efficacy Signal Of Genomically-matched Therapiesmentioning
confidence: 99%
“…Another phase-1/2 study of the irreversible pan-FGFR inhibitor (FGFR 1-4), TAS-120, futibatenib, enrolled 45 chemotherapy-refractory CCA patients harbouring FGFR aberrations (FGFR2 fusions, mutations, amplifications or re-arrangements) and resulted in an ORR of 25% and a disease control rate (DCR) of 78.6%. Interestingly, 13 patients received prior treatment with at least one reversible FGFR-inhibitor, and of those, four patients achieved a partial response [ 17 , 18 ].…”
Section: Potential Clinical Applications Of Molecular Profilingmentioning
confidence: 99%
“…NA: not available. Drug ( Mechanism of Action ) Target Phase Total Number of CCA Patients Enrolled Outcome in CCA Pemigatinib ( FGFR1-3 inhibitor ) FGFR alterations 2 146 ORR = 36% CR ( n = 3) PR ( n = 35) DOR > 12 mo ( n = 7) [ 13 , 14 ] Infigratinib ( FGFR1-3 inhibitor ) FGFR2 fusions 2 61 ORR = 14.8% PFS = 5.8 mo [ 15 ] Futibatenib ( FGFR 1-4 inhibitor ) FGFR2 fusions, mutations, amplifications or re-arrangements 1/2 45 ORR = 25% PR ( n = 4) [ 17 , 18 ] Futibatenib ( FGFR 1-4 inhibitor ) FGFR alterations + acquired resistance to FGFR inhibitors N/A 6 PR ( n = 2) SD ( n = 2) [ 19 ] Ivosidenib ( IDH1 inhbitor ) IDH1 mutations 3 185 ORR = 2.4% PFS = 32% at 6 mo; 21.9% at 12 mo; OS = 9.7 mo [ 20 ] …”
Section: Table A1mentioning
confidence: 99%